Navigating Institutions for Integration: Perceived Institutional Barriers of Access to the Labour Market among Refugee Women in Sweden. (6th February 2021) - Spehar, Andrea
Abstract: Sweden may in many respects be regarded as one of the most gender-equal countries in the world today. However, when looking at the situation of immigrant women a more unsettling picture emerges. Employment rates illustrate large gaps between native and immigrant women, as well as significant gender gaps between immigrant men and women. When investigating plausible explanations for underrepresentation of immigrant women in the labour market, scholars have mainly focussed on cultural and individual explanatory factors. In contrast, this article casts our analytical gaze towards institutional factors by examining the experiences of refugee women who, despite expressing a positive attitude and strong willingness to establish themselves on the Swedish labour market, had not succeeded in finding secure employment. Drawing upon in-depth interviews with refugee women, the results suggest that the insufficient institutional support during the first years in Sweden, devaluation of competence and challenges with 'starting over' are perceived as central barriers hindering their access to the Swedish labour market. To facilitate higher labour force participation among refugee women in Sweden it is crucial to develop and implement gender-sensitive measures that target different groups of immigrant women and meet their distinct experiences, needs, and interests.